2007
DOI: 10.1007/s00415-006-0341-6
|View full text |Cite
|
Sign up to set email alerts
|

Pusher Syndrome – a frequent but little-known disturbance of body orientation perception

Abstract: Disturbances of body orientation perception after brain lesions may specifically relate to only one dimension of space. Stroke patients with "pusher syndrome" suffer from a severe misperception of their body's orientation in the coronal (roll) plane. They experience their body as oriented 'upright' when it is in fact markedly tilted to one side. The patients use the unaffected arm or leg to actively push away from the un-paralyzed side and resist any attempt to passively correct their tilted body posture. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 57 publications
1
63
0
10
Order By: Relevance
“…Pusher syndrome is perceived as a little-known neurological disorder [5]. A critical appraisal of publications has been carried out, based on the PubMed database [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pusher syndrome is perceived as a little-known neurological disorder [5]. A critical appraisal of publications has been carried out, based on the PubMed database [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by tilt (20-35 degrees) towards the contralesional paretic side [1][2][3][4][5]. Resistance to passive external correction of posture to an upright position is an important symptom of pusher syndrome [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Karnath et al found 5 patients with severe PB (SCP=6) who experience their body as being oriented "upright" when it is actually tilted about 18° towards the side of the brain lesion and with no SVV bias (Karnath et al, 2000b). According to the authors, the possible explanation for the PB is that when patients try to move their body to a subjectively 'upright' position, they became laterally unstable because their center of mass was shifted too far to the ipsilesional side and they react to this imbalance by pushing themselves to the contralesional side (Karnath et al, 2000b;Karnath, 2007). In contrast, Pérrenou et al recently found a contralesional bias of SPV in 6 pusher patients with an SCP score ranging from 3 to 6.…”
Section: Postural Controlmentioning
confidence: 99%